2022
DOI: 10.1186/s12887-022-03359-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental outcomes of infants born to mothers with SARS-CoV-2 infections during pregnancy: a national prospective study in Kuwait

Abstract: Background An increasing proportion of women are infected with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) during pregnancy. Intrauterine viral infections induce an increase in the levels of proinflammatory cytokines, which inhibit the proliferation of neuronal precursor cells and stimulate oligodendrocyte cell death, leading to abnormal neurodevelopment. Whether a maternal cytokine storm can affect neonatal brain development is unclear. The objective of the present study was t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Research into the long-term consequences of COVID-19 in pregnancy for mothers and newborns is still scarce. Initial, preliminary reports of the long-term effects of maternal COVID-19 infection during pregnancy have suggested worrying adverse neurodevelopmental sequelae [24][25][26] . These cases highlight the urgent need for data on measures to limit maternal infection, which may have as yet unknown adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Research into the long-term consequences of COVID-19 in pregnancy for mothers and newborns is still scarce. Initial, preliminary reports of the long-term effects of maternal COVID-19 infection during pregnancy have suggested worrying adverse neurodevelopmental sequelae [24][25][26] . These cases highlight the urgent need for data on measures to limit maternal infection, which may have as yet unknown adverse consequences.…”
Section: Discussionmentioning
confidence: 99%
“…Initial, preliminary reports of the long-term effects of maternal COVID-19 infection during pregnancy on child health, and worrying adverse neurodevelopmental sequelae [24][25][26] have appeared. These cases highlight the potential adverse consequences of maternal COVID-19 disease and the urgent need for data on measures to limit maternal infection.…”
Section: Discussionmentioning
confidence: 99%
“…Data on earlier exposure to the inflammatory stress associated with maternal SARS-CoV-2 infection would have been interesting. Ayed et al 4 reported increased abnormal ASQ scores in infants exposed during the first or second trimester. This 10-month follow-up reassuringly suggested that these infants had not experienced major neurodevelopmental delays after in utero exposure to SARS-CoV-2.…”
Section: Neurodevelopmental Status Was Measured By the Validatedmentioning
confidence: 99%